Spatial and temporal analysis of rainfall concentration using the Gini index and PCI - Sangüesa, Claudia; Pizarro, Roberto; Ibañez, Alfredo; Pino, Juan; Rivera, Diego; García-Chevesich, Pablo; Ingram, Benjamin R. (MDPI, 2018)
This study aims to determine if there is variation in precipitation concentrations in Chile. We analyzed daily and monthly records from 89 pluviometric stations in the period 1970–2016 and distributed between 29°12′ S and 39°30′ S. This area was divided into two climatic zones: arid–semiarid and humid–subhumid. For each station, the Gini coefficient or Gini Index (GI), the precipitation concentration index (PCI), and the maximum annual precipitation intensity in a 24-h duration were calculated. These series of annual values were analyzed with the Mann–Kendall test with 5% error. Overall, it was noted that positive trends in the GI are present in both areas, although most were not found to be significant. In the case of PCI, the presence of positive trends is only present in the arid–semiarid zone; in the humid–subhumid zone, negative trends were mostly observed, although none of them were significant. Although no significant changes in all indices are evident, the particular case of the GI in the humid–subhumid zone stands out, where mostly positive trends were found (91.1%), of which 35.6% were significant. This would indicate that precipitation is more likely to be concentrated on a daily scale.
Keywords: Precipitation concentration; Rainfall Gini Index; Precipitation trends; Trends of monthly and daily precipitation; 24h maximum intensity